Lycopene attenuates western-diet-induced cognitive deficits via improving glycolipid metabolism dysfunction and inflammatory responses in gut–liver–brain axis - Wang, Jia; Wang, Zhuo; Li, Bing; Qiang, Yu; Yuan, Tian; Tan, Xintong; Wang, Zihan; Liu, Zhigang; Liu, Xuebo (International Journal of Obesity, 2019)
Background/objectives The aim of the current study was to investigate the inhibitory effect of lycopene (LYC), a major carotenoid present in tomato, on high-fat and high-fructose western diet (HFFD)-induced cognitive impairments and the protective effects on HFFD-elicited insulin resistance, lipid metabolism dysfunction and inflammatory responses in the gut–liver–brain axis. Subjects/methods We randomly assigned 3-month-old C57BL/6 J mice to three groups with different diets: the control group, HFFD group and HFFD + LYC group (LYC, 0.03% w/w, mixed into high-fat diet) for 10 weeks. Results The results of the Y-maze task and Morris water maze tests demonstrated that LYC attenuated HFFD-induced memory loss. Moreover, LYC suppressed HFFD-elicited synaptic dysfunction and increased the expressions of SNAP-25 and PSD-95. Furthermore, LYC ameliorated insulin resistance, lipid metabolism dysfunction and inflammatory responses in the mouse brain and liver. LYC also prevente.d intestinal barrier integrity damages and decreased the level of circulating LPS. Conclusions These results demonstrated that LYC ameliorated HFFD-induced cognitive impairments in a mouse model by improving insulin resistance, lipid metabolism dysfunction and inflammatory responses in the gut–liver–brain axis. These findings indicate that LYC might be a nutritional strategy for western diet-induced dysfunction of the central nervous system.